Consensus document of the Spanish Society of Paediatric Infectious Diseases and the Advisory Committee on Vaccines of the Spanish Association of Pediatrics for vaccination of immunosuppressed individuals - Irene Rivero Calle; Teresa del Rosal Rabes; Elisa Garrote Llanos; Esmeralda Núñez Cuadros; María Luisa Navarro Gómez; José Tomás Ramos Amador; Cristina Calvo; Francisco Álvarez García (Elsevier, 2023)
The number of people with immunosuppression is increasing considerably due to their greater survival and the use of new immunosuppressive treatments for various chronic diseases. This is a heterogeneous group of patients in whom vaccination as a preventive measure is one of the basic pillars of their wellbeing, given their increased risk of contracting infections. This consensus, developed jointly by the Sociedad Española de Infectología Pediátrica (Spanish Society of Pediatric Infectious Diseases) and the Advisory Committee on Vaccines of the Asociación Española de Pediatría (Spanish Association of Paediatrics), provides guidelines for the development of a personalised vaccination schedule for patients in special situations, including general recommendations and specific recommendations for vaccination of bone marrow and solid organ transplant recipients, children with inborn errors of immunity, oncologic patients, patients with chronic or systemic diseases and immunosuppressed travellers. Resumen: El número de personas con inmunodepresión está aumentando considerablemente debido a su mayor supervivencia y al empleo de nuevas terapias inmunosupresoras en diversas patologías crónicas. Se trata de un grupo heterogéneo de pacientes en los que la vacunación como arma preventiva supone uno de los pilares básicos de su bienestar, por su elevado riesgo a padecer infecciones. Este consenso, elaborado conjuntamente entre la Sociedad Española de Infectología Pediátrica (SEIP) y el Comité Asesor de Vacunas de la Asociación Española de Pediatría (CAV-AEP), aporta unas directrices para programar un calendario adaptado a cada paciente en situaciones especiales que incluye recomendaciones generales, vacunación en pacientes con trasplante de médula y trasplante de órgano sólido, vacunación en niños con errores innatos de la inmunidad, vacunación en el paciente oncológico, vacunación en pacientes con enfermedades crónicas o sistémicas y vacunación en niños viajeros inmunodeprimidos.